Poverty Alleviation Policies Based On Strengthening The Economy Of The Underprivileged Community In Makassar City - Rasidin Calundu; Syamsiah Syamsiah (Pasundan Social Science Development, 2025)
This qualitative research utilised a phenomenological approach. The results of the study indicate that Poverty is influenced by various economic, social and environmental factors. Rapid urban development has not been accompanied by equitable access to employment, income and basic services, resulting in pockets of poverty remaining scattered, particularly in densely populated settlements and informal areas. Many people work in the informal sector with unstable incomes, while limited education, skills, and poor housing conditions exacerbate their situation. Overall, poverty in Makassar is multidimensional and requires a comprehensive approach. Government policies focus on empowerment, such as training for MSMEs, increasing access to capital, forming business groups, digitising MSMEs, and strengthening education and basic infrastructure. These policies aim to ensure that marginalised communities do not only receive temporary assistance, but are able to develop businesses and increase their income independently. Poverty reduction strategies should focus on empowering MSMEs, expanding access to inclusive capital, strengthening the community economy, digitising micro-businesses, and improving education and economic literacy. The restructuring of slum areas and improvement of basic infrastructure also support the productivity of marginalised communities.